Transference and Subjective Implication: Psychoanalytic Reflections on an Action Research - Souza, Mariana Mayumi; Paes de Paula, Ana Paula (Organizações & Sociedade, 2021)
This paper aims to use the Freudian psychoanalytic approach to explain the process of interaction between researchers and subjects participating in action research, bringing a new contribution to organizational studies. It is hoped that this research will promote the self-reflection of researchers in this research process, highlighting the complexities of the transferential dynamics and subjective implication of field interactions. With this objective in mind, key psychoanalytic concepts are explored and definitions of action research are presented. This is achieved by describing how it was carried out in a waste pickers’ association, as well as how the reciprocal influences between the subjects participating in the research are constituted and the constituents of the research and its results, through an analysis of the transferential dynamics and subjective implications between those involved.